PROBIOTICS, PREBIOTICS AND SNYBIOTICS IN POULTRY MODE OF ACTION, LIMITATION, AND ACHIEVEMENTS - Agata DANKOWIAKOWSKA; Izabela KOZLOWSKA; Marek BEDNARCZYK (Journal of Central European Agriculture, 2013)
The withdrawal of antibiotic growth promoters from poultry industry have forced farmers to seek alternatives for the posing a risk factors of cross-resistance acquisition by harmful bacteria. A particular nuisance became salmonellosis and campylobacteriosis forcing to the elimination of whole poultry flocks as well as causing dangerous zoonotic diseases in humans. An excellent replacement for antibiotics have become the pro-, pre-and synbiotic substances which have a beneficial effect on the host organism through the development intensification of healthy intestinal microbial strains and the elimination of pathogenic strains. Such preparations may be administered both in the water spray as well as in feed. Excellent and promising method appears to be their injection directly into the egg air chamber in the 12th day of incubation. However, further studies are required to determine the appropriate doses as well as combinations of bioactive substances and to determine the optimal way for their delivery.